Take the 2-minute tour ×
Mathematics Stack Exchange is a question and answer site for people studying math at any level and professionals in related fields. It's 100% free, no registration required.

I am preparing myself to the mini-exam in measure theory by solving problems from lecturer's notes and I have encountered some difficulties I cannot overcome. I would appreciate if you could solve the following (or if you could give me some huge hints at least):

Let $\mu$ be the Lebesgue measure on $\mathbb{R}$ and let $E$ be a Borel subset of $\mathbb{R}$ such that $$\mu(E\setminus (E+x))=0$$ for any $x\in\mathbb{R}$, where $E+x=\{z+x\mid z\in E\}$. Prove that $\mu(E)=0$ or $\mu(\mathbb{R}\setminus E)=0$.

I know that $\mu(E)=\mu(E+x)$ and I suppose I have to prove the statement by assuming the opposite, but I really do not know how. Thanks in advance!

share|improve this question
add comment

2 Answers 2

up vote 5 down vote accepted

If $\mu(E) \not=0$ and $\mu(E^c) \not=0$ (here $E^c = \mathbb R \setminus E$), we can choose intervals $I$ and $J$ such that $\mu(I\cap E) \geq (3/4) \mu(I)$ and $\mu(J\cap E^c) \geq (3/4) \mu(J)$. By shrinking either $I$ or $J$ if necessary, we can take $\mu(I) = \mu(J)$, i.e. $I$ and $J$ have the same length. Then we can choose $x$ such that $J+x = I$. But then $I \cap E \cap (E^c + x)$ is a subset of $E\cap (E^c +x) = E\setminus (E+x)$, and we have

$$\mu(I \cap E \cap (E^c + x)) \geq \mu(I \cap E) + \mu(I \cap (E^c + x)) - \mu(I) ,$$

by elementary set theory and since $I\supset (I \cap E) \cup(I \cap (E^c + x))$. We have $\mu(I\cap (E^c + x)) = \mu(J\cap E^c)$, and so

$$\mu(I \cap E \cap (E^c + x)) \geq (3/4) \mu(I) + (3/4)\mu(I) - \mu(I) = (1/2)\mu(I) > 0 .$$

Thus $E\setminus (E+x)$ has positive measure.

share|improve this answer
add comment

I would like to give another proof I have found recently after being told to make use of Fubini's theorem.

Since $\mu(E\setminus E+x)=0$ for all $x\in\mathbb{R}$, we have $$\begin{align} 0=\int\limits_{\mathbb{R}}\mu(E\setminus (E+x))\,\text{d}\mu(x)=&\int\limits_{\mathbb{R}}\int\limits_{\mathbb{R}}\chi_{E\setminus (E+x)}(s)\, \text{d}\mu(s)\,\text{d}\mu(x)\\=&\int\limits_{\mathbb{R}}\int\limits_{\mathbb{R}}\chi_E(s)\left(1-\chi_{E+x}(s)\right)\,\text{d}\mu(s)\,\text{d}\mu(x)\\=&\int\limits_{\mathbb{R}}\int\limits_{\mathbb{R}} \chi_E(s)\left(1-\chi_{E+x}(s)\right)\,\text{d}\mu(x)\,\text{d}\mu(s)\\=&\int\limits_{\mathbb{R}}\chi_E(s)\left(\int\limits_{\mathbb{R}}\left(1-\chi_{E-s}(x)\right)\,\text{d}\mu(x)\right)\,\text{d}\mu(s)\\=&\int\limits_{\mathbb{R}}\chi_E(s)\left(\int\limits_{\mathbb{R}}\chi_{(E-s)^c}(x)\,\text{d}\mu(x)\right)\,\text{d}\mu(s)=\int\limits_{\mathbb{R}}\chi_E(s)\mu\left((E-s)^c\right)\,\text{d}\mu(s)\\=&\int\limits_{\mathbb{R}}\chi_E(s)\mu\left(E^c\right)\,\text{d}\mu(s)=\mu\left(E^c\right)\int\limits_{\mathbb{R}}\chi_E(s)\,\text{d}\mu(s)=\mu(E^c)\mu(E). \end{align}$$ Therefore either $\mu(E)$ or $\mu(\mathbb{R}\setminus E)$ is $0$.
Notice that we used Fubini's theorem only once while changing the order of integration in equality no. 4. The eighth equality follows from the translation invariance of Lebesgue mesure.

share|improve this answer
add comment

Your Answer

 
discard

By posting your answer, you agree to the privacy policy and terms of service.

Not the answer you're looking for? Browse other questions tagged or ask your own question.